ANALISA BEBAN BIAYA DAN WAKTU PERAWATAN LUKA KAKI DIABETIK (LKD) GANGREN UNIT PELA Y ANAN HOME CARE: RETROSPECTIVE COHORT STUDY - Sukmawati, Sukmawati; Laitung, Baharia; Irwan, Muhammad; Rassa, Syaiful; Yusuf, Saldy (Jurnal Luka Indonesia, 2016)
Background: Diabetic foot ulcer (DFU) gangrene is commonly chronic wound in home care setting, it takes high cost and long term care. Aim: The aims of this study was to evaluate burden time and cost of DFU gangrene. Method: This was a retrospective cohort study conducted from 2011-2014. Burden cost including material, nursing, and dressing cost. While burden time including duration, frequency , and interval of care. All participants categorized into DFU non gangrene and gangrene. Data analyzed using Chi Square or Fisher exact test using SPSS 16.0 (SPSS, Inc. Chicago, IL). Results: Forty eight participants included in this study (43 DFU non gangrene and 5 DFU gangrene) with mean age were (58.8 SD ± 9.7 vs 60 SD ± 11.3 years) respectively . Nursing cost (Rp. 123.412 vs Rp. 218.653) and dressing cost (Rp. 243.844 vs Rp. 711.558) were lower for DFU non gangrene. Wound care shorter for non gangrene (27.3 vs 91.8 days), dressing change less frequently (7.5 vs 21.6 times) and interval dressing change was equal (3.5 vs 3.2 days) respectively . Conclusion: There are different burden cost and burden time between DFU non gangrene and DFU gangrene clinically. Keywords: diabetic foot ulcers, gangrene, burden cost, burden time, home care.